Parâmetros ecofisiológicos de podocnemis expansa: efeito dos avanços da agropecuária - Porto, Juliane Nancy Lima (Universidade Federal do Tocantins, 2019)
Due to the importance of agriculture in the North and Central-West Region, distribution sites of the species Podocnemis expansa, the objective was to study if the impacts caused by the advancement of agriculture and livestock can affect the environment to the point of interfering with the optimal temperature of performance of these animals. With this, the performance curve of this species was elaborated, in order to understand the optimum temperature for its performance, comparing individuals of natural environment and commercial production. In addition, the analysis of land use and occupation in the Araguaia Basin was conducted between 1985 and 2017 to show the progress of the agricultural sector. An analysis was also made of the variations in flow and precipitation levels in the Alto Araguaia Basin, in the same time cut, in which it was possible to identify possible changes in the flow caused by the agricultural practice. The ecophysiological study was carried out in the municipality of Lagoa da Confusão - OT in the period of ebbing season of 2018. Animals were collected from natural environment and captivity, these individuals were submitted to low and high temperatures aiming to find the minimum and maximum critical, respectively, in addition to be submitted to 6 test batteries at 3 different temperatures to compose the locomotor performance curve. Each battery consisted of timing the swim time on a 2 meter course. With the value of the minimum and maximum critical temperature it was possible to compose the graph along with these results. For the analysis of land use and occupation, maps of the years of 1985, 1996, 2006, and 2017 of the Araguaia River Basin were elaborated. The maps were obtained through the MapBiomas Project, processed and treated in Qgis software. For the analysis of flow and rainfall, rainwater and rainfall data were collected from 24 and 34 stations, respectively, on the HidroWeb platform of the National Water Agency, inserted in the Alto Araguaia Basin, in order to obtain the time series decomposition, detecting the effects of seasonality and trends in flow and precipitation variation. The data were corrected using Amelia package and tested by means of mixed effects linear models (LMMs) the ratio of river flow with the percentage area occupied by agriculture in the ANA level 4 ottobacias. The result obtained with regard to the locomotor performance of the P. expansa turtle indicates a significant difference (P <0.001) in the locomotor performance curve between individuals from both environments. Commercial turtle turtles showed inferior performance compared to wild-type animals, however, it was observed that captive animals had a better performance at higher temperatures. Concerning the use and occupation of the soil in the Araguaia River Basin, an increase of over 8 million ha was observed. There was a significant difference between the flow and precipitation levels over the years, and a significant negative relation between the area occupied by agriculture and the average flow of the Alto Araguaia Basin. From the results obtained, it was known that the advance of the area occupied by agriculture affects the environment of survival of P. expansa and that the species presents a thermoforming behavior, indicating that a severe increase in temperature could lead the species to extinction, since it does not have thermoregulatory behavior.